Socio‐economic status and quality of life in children with chronic disease: A systematic review. (December 2016) - Didsbury, Madeleine S; Kim, Siah; Medway, Meredith M; Tong, Allison; McTaggart, Steven J; Walker, Amanda M; White, Sarah; Mackie, Fiona E; Kara, Tonya; Craig, Jonathan C; Wong, Germaine
Abstract: Reduced quality of life (QoL) is a known consequence of chronic disease in children, and this association may be more evident in those who are socio‐economically disadvantaged. The aims of this systematic review were to assess the association between socio‐economic disadvantage and QoL among children with chronic disease, and to identify the specific socio‐economic factors that are most influential. MEDLINE, Embase and PsycINFO were searched to March 2015. Observational studies that reported the association between at least one measure of social disadvantage in caregivers and at least one QoL measure in children and young people (age 2–21 years) with a debilitating non‐communicable childhood disease (asthma, chronic kidney disease, type 1 diabetes mellitus and epilepsy) were eligible. A total of 30 studies involving 6957 patients were included (asthma (six studies, n = 576), chronic kidney disease (four studies, n = 796), epilepsy (14 studies, n = 2121), type 1 diabetes mellitus (six studies, n = 3464)). A total of 22 (73%) studies reported a statistically significant association between at least one socio‐economic determinant and QoL. Parental education, occupation, marital status, income and health insurance coverage were associated with reduced QoL in children with chronic disease. The quality of the included studies varied widely and there was a high risk of reporting bias. Children with chronic disease from lower socio‐economic backgrounds experience reduced QoL compared with their wealthier counterparts. Initiatives to improve access to and usage of medical and psychological services by children and their families who are socio‐economically disadvantaged may help to mitigate the disparities and improve outcomes in children with chronic illnesses.